Pollen, NPP, macro- and micro-charcoal , macroremains and LOI records from the southern border of the East-European forest-steppe (study site Omelchenki) - Ekaterina Lukanina; Lyudmila S Shumilovskikh (PANGAEA, 2023)
Omelchenki study site is located at the southern border of the East-European forest-steppe ecotone next to the village of Omelchenki in the Zmiiv district of the Kharkiv region, Ukraine (49.63969 N, 36.41677 E, 88 m a.s.l.). The sediment core was obtained from a peatbog ~3 km south and west from the Siverskyi Donets River channel, in May 2013 (2013-05-05) and consists of two sister cores – Omelchenki I (0-150 cm) and Omelchenki II (25-175 cm). The two cores were taken close to each other with overlapping segments with a Russian corer. Based on the LOI results we combined the first 25 cm of the Omelchenki I core with the main Omelchenki II core to obtain a continuous record of Omelchenki. This work was aimed to reconstruct the southern tree line dynamics and vegetation changes in Eastern Europe during the Holocene due to climate change, fires and human activities. It contains unique for the East-European forest-steppe palynological data covering the last ~9,800 years. To determine the chronology, 9 AMS radiocarbon dates were carried out in the AMS Radiocarbon Laboratories in Poznan, Poland and the Institute of Physics of the University of Erlangen Nuremberg, Germany. The radiocarbon ages were calibrated and the age-depth model was built using the R package extquotesinglebacon extquotesingle based on Bayesian statistics (Blaauw and Christen, 2011; doi:10.1214/11-BA618) with the IntCal20 calibration curve for the Northern Hemisphere (Reimer et al., 2020; doi:10.1017/RDC.2020.41).